Needs analysis of breastfeeding support applications - Andhini, Citra Setyo Dwi; Romadho, Lily Wahyuni; Utami, Rina; Putri, Tantri Maulani (Science Midwifery, 2025)
The WHO recommends exclusive breastfeeding for the first six months and continued breastfeeding until two years of age or beyond. However, many inhibiting factors remain, such as limited knowledge, lack of support from family and healthcare professionals, and psychological and social barriers that impact breastfeeding success. This study aims to analyze the need for breastfeeding support apps among mothers. This is a qualitative study with an exploratory descriptive approach. In-depth interviews were conducted with 10 mothers who have breastfed and healthcare professionals, with questions related to mothers' personal experiences while breastfeeding, information sources used, information needs, needs for breastfeeding education apps, expectations and suggestions. The results of this study identified five themes: physical and emotional challenges in breastfeeding, the need for practical and specific information, trust in information sources, preferences for digital educational media, and expectations for educational apps. Through this study, it can be concluded that mothers need support from all parties, including healthcare professionals, with short video and visual educational media aligned to support breastfeeding practices.